YiQiFuMai Powder Injection Attenuates Coronary Artery Ligation-Induced Heart Failure Through Improving Mitochondrial Function via Regulating ROS Generation and CaMKII Signaling Pathways - Zhang, Yu; Zhang, Ling; Zhang, Yan; Fan, Xiaoxue; Yang, Weiwei; Yu, Boyang; Kou, Junping; Li, Fang (Frontiers in Pharmacology, 2019)
The YiQiFuMai powder injection (YQFM), a traditional Chinese medicine prescription re-developed based on Sheng-Mai-San, is widely applied for the treatment of cardiovascular diseases. However, its potential molecular mechanism remains obscure. The present study was designed to observe the effects of YQFM and underlying mechanisms on coronary artery ligation (CAL)-induced heart failure (HF) and cell hypoxia of 24 hours’ oxygen-glucose deprivation (OGD) in neonatal rat ventricular myocytes (NRVMs). HF was induced by permanent CAL for 2 weeks in ICR mice. The results demonstrated that YQFM significantly attenuated CAL-induced HF via improving the cardiac function, cardiac systolic function, cardiac structure impairment, cardiac histological features and fibrosis. YQFM markedly attenuated mitochondrial dysfunction through improving mitochondrial morphology, increasing mitochondria membrane potential (Δψm), mitochondrial ROS generation and expression of Mitofusin2 (Mfn2), meanwhile, decreasing phosphorylation of dynamin-related protein l (p-Drp1). Mechanistically, YQFM could significantly decrease the expression of isoforms of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase subunit NADPH oxidase 2 (NOX2), p67phox and NADPH oxidase 4 (NOX4), ultimately reducing reactive oxygen species (ROS) generation. In addition, YQFM could down-regulate expression of calcium voltage-gated channel subunit α1C (CACNA1C) and phosphorylation of calmodulin dependent protein kinase II (p-CaMKII). These results suggest that YQFM ameliorates mitochondrial function in HF mice, partially through inhibiting ROS generation and CaMKII signaling pathways. Therefore, the present study provided scientific evidence for the underlying mechanism of YQFM.